A new species of Cymodoce from Iran (Crustacea: Isopoda: Sphaeromatidae) with remarks on the status of Cymodoce manorii (Nooruddin, 1965) comb. nov. and Cymodoce spinula Yousuf & Javed, 2001 - Khalaji-Pirbalouty, Valiallah (Zootaxa, 2016)
Cymodoce brucei sp. nov. is described from the intertidal zone of the Iranian coast of the Oman Sea. This species can be distinguished from all other Cymodoce in the Western Indian Ocean region, by a pleotelson with a large prominent tongue-like projection in midline of the posterior margin. The status of Cerceis manorii Nooruddin, 1965, and Cymodoce spinula Yousuf & Javed, 2001 both from Pakistan (Karachi) is determined and Cymodoce manorii (Nooruddin, 1965) comb. nov. is established.